2008
DOI: 10.1620/tjem.215.133
|View full text |Cite
|
Sign up to set email alerts
|

Memory Impairment and Awareness of Memory Deficits in Early-Stage Alzheimer's Disease

Abstract: In addition to their memory impairment, individuals with Alzheimer's disease (AD) often suffer from deficits in self-awareness. Awareness of memory deficits or metamemory is a multifaceted function, comprising on-line self-monitoring, generalized self-beliefs of memory efficacy, and generalized knowledge about memory functions. Awareness of memory problems in early-stage AD is a matter of clinical importance from a humanistic point of view, because higher levels of awareness may be associated with better futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 30 publications
3
39
0
1
Order By: Relevance
“…Indeed, by capitalizing on efficient and deep encoding based on iterative cued immediate recall of the target name, we involuntary expose our patients to their memory recall failures for name materials. That is, we consider the hypothesis that our encoding procedure has triggered transient awareness of (Duke et al, 2002;Mimura and Yano, 2006;Schmitter-Edgecombe and Seelye, 2011;Stewart et al, 2010). Importantly, previous studies that have assessed online metacognitive predictions of recognition performance in patients with Mild Cognitive Impairment (MCI) and AD patients have used a traditional FOK paradigm, in which the participants experience recall failure before indicating their FOK judgments.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, by capitalizing on efficient and deep encoding based on iterative cued immediate recall of the target name, we involuntary expose our patients to their memory recall failures for name materials. That is, we consider the hypothesis that our encoding procedure has triggered transient awareness of (Duke et al, 2002;Mimura and Yano, 2006;Schmitter-Edgecombe and Seelye, 2011;Stewart et al, 2010). Importantly, previous studies that have assessed online metacognitive predictions of recognition performance in patients with Mild Cognitive Impairment (MCI) and AD patients have used a traditional FOK paradigm, in which the participants experience recall failure before indicating their FOK judgments.…”
Section: Discussionmentioning
confidence: 99%
“…The neurobiological mechanisms underlying unawareness have not been clearly determined. Studies with positron emission tomography (PET) [5,6] or single photon emission CT (SPECT) [7][8][9][10][11] have suggested that impaired awareness may be related to cerebral dysfunction involving the frontal and right hemisphere regions of the brain. However, most of these studies examined mild or moderate AD patients with several neuropsychiatric symptoms, such as depression, apathy, delusion, and disinhibition.…”
mentioning
confidence: 99%
“…AD is a progressive neurodegenerative disorder that with time impairs cognitive skills and learning and memory abilities (Mimura, 2008). The main pathogenic mechanisms responsible for AD include cholinergic dysfunction, enhanced oxidative stress burden and disturbed antioxidant defense system, augmented inflammatory response, and an excitotoxic insult (Grothe et al, 2014;Obulesu and Jhansilakshmi, 2014;Subash et al, 2014).…”
Section: Introductionmentioning
confidence: 99%